Towards application of thermal infrared imaging in medical diagnosis: protocols and investigations - Arthur, Daniel T.J. (Curtin University, 2014)
This thesis ‘Thermal Infrared Imaging: Advancement for Clinical Applications’ documents a series of clinical and laboratory investigations into: development and application of protocols for objective acquisition and processing of clinical TIRI image data, characterisation of human tissue emissivity within clinically-relevant regimes, and use of thermal infrared imaging to determine the depth of subcutaneous heat sources. This work was supported by the Australian Defence Science & Technology Organisation, Western Australian Department of Health, and Flir Systems.